BREASTFEEDING STATUS AND ITS DUAL INFLUENCE ON INFANT ANTHROPOMETRIC DEVELOPMENT AND MATERNAL MENTAL HEALTH IN AFIKPO NORTH, EBONYI STATE - Orji, Esther Ukwuoma (African Journal of Social and Behavioural Sciences, 2025)
The mental and psychological well-being of mother-infant relationships under six months of age indicates good anthropometric outcomes and serves as a measure against growth-related comorbidities, demanding continuous, sustained attention. Researching on that would advance the promotion of sustainable policies towards optimal breastfeeding practices among mothers across states, thereby making Nigeria a global player. This study evaluated the relationship between the breastfeeding status of children under six months of age and their anthropometry outcome considering the psychological well-being of their mothers. Using MUAC (Mid-Upper Arm Circumference) and weight measuring instruments, data was collected and correlated with the mothers’ psychological well-being score. Pearson r correlation statistics was used for data analysis. The result showed that MUAC outcome and body weight did not differ between exBF (Exclusive breastfeeding) and non-exBF (non-exclusive breastfeeding) infants throughout the first six months of life. However, exBF mothers reported higher psychological wellbeing (r = p˂.05 = .21) than their counterparts (r = p˂.05 = .03) on MUAC outcome measurement, and it was significant. The result also evidenced that exBF mothers reported higher psychological well-being (r = p˂.01 = .13) than their counterparts (r = p˂.01 = .01) on the outcome of their child’s body weight and was also significant. It was concluded that infants in the early stage of life may display similar growth patterns despite the breastfeeding status, but mothers who practice exBF tend to experience greater postpartum maternal psychological well-being. Implications of the study and recommendations were made.